Sero-prevalence of anti-SARS-CoV-2 antibodies among communities between July and August 2022 in Bangui, Central African Republic - Alexandre Manirakiza; Christian Malaka; Jean de Dieu Longo; Brice Martial Yambiyo; Saint-Calver Henri Diemer; Joella Namseneï; Cathy Sandra Gomelle Coti-Reckoundji; Modeste Bouhouda; Marie Roseline Darnycka Belizaire; Jean Baptiste Roungou; Narcisse Patrice Komas; Gérard Grésenguet; et al. (AOSIS, 2023)
Background. Large-scale population-based seroprevalence studies of SARS-CoV-2 are essential to characterize the cumulative incidence of SARS-CoV-2 infection and to extrapolate the prevalence of presumptive immunity at the population level. Objective. The objective of our survey was to estimate the cumulative population immunity for COVID-19 and to identify individual characteristics associated with positive serostatus. Materials and Methods. This was a clustered cross-sectional study conducted from July 12 to August 20, 2021, in households in the city of Bangui, the capital of the Central African Republic. Information regarding demographic characteristics (age, gender, and place of residence), and comorbidities (chronic diseases) was collected. A venous blood sample was obtained from each participant to determine the level of total anti-SARS-CoV-2 antibodies using a WANTAI SARS-CoV-2 Ab ELISA kit. Results. All up, 799 participants were surveyed. The average age was 27 years, and 45.8% of the respondents were male (sex ratio: 0.8). The overall proportion of respondents with positive serostatus was 74.1%. Participants over 20 years of age were twice as likely to have positive serostatus, with an OR of 2.2 [95% CI: (1.6, 3.1)]. Conclusions. The results of this survey revealed a high cumulative level of immunity in Bangui, thus indicating a significant degree of spread of SARS-CoV-2 in the population. The public health implications of this immunity to SARS-CoV-2 such as the post-vaccination total antibody kinetics remain to be determined.